LRS Bianchi Type-II modified holographic Ricci dark energy models in a scalar-tensor theory of gravitation. Issue 1 (2nd January 2017) - Reddy, D.R.K.; Kanakavalli, T.; Rao, G. Ananda
Abstract: A locally rotationally symmetric (LRS) Bianchi type- II spacetime is considered in the presence of dark matter and anisotropic modified holographic Ricci dark energy in the scalar-tensor theory of Saez and Ballester (Phys. Lett. A 113: 467, 1986). To obtain exact solutions of Saez-Ballester gravitational field equations we use the following physically significant conditions: (i) the scalar expansion of the space time is proportional to its shear scalar, (ii) hybrid expansion law for the scale factor proposed by Akarsu et al. (JCAP 01: 022, 2014) and (iii) modified Ricci dark energy density given by Chen and Jing (Phys. Lett. B 679: 144, 2009). The solution describes modified holographic Ricci dark energy models, in this theory, which exhibit a smooth transition from decelerated phase to the present accelerated phase of the universe. This result is in accordance with the present day observations of cosmology. The dynamical parameters of the models are computed and their physical importance, in cosmology, is discussed.